Dynamics Analysis of Wind Turbine Gearbox based on Full Drivetrain - Ma Xiaoguang; Yu Tianlong; Bao Yanqiu; Li Zheng (Jixie chuandong)
The gearbox is a pivotal component in wind turbine,the dynamics performance of gearbox is one of the most critical factors determining the lifetime of gearbox and that of the wind turbine. A multi-body dynamics drivetrain model with rigid-flexible body coupled of a level MW wind turbine is built by using the Simpack software. The reliability and accuracy of this model is confirmed through comparing the nature frequency derived from Simpack drivetrain model and the nature frequency calculated by Bladed software and traditional approach. The modal analysis and torsional resonance analysis of gearbox is completed based on the multi-body dynamics simulation both in frequency domain and time domain,furthermore,the potential resonance is evaluated,the influence of shaft misalignment on the dynamics performance of gearbox is analyzed. The aforementioned analysis approach and evaluation method is confirmed to be correct by experimental.